COMPUTER MICROSCOPY OF MATERIALS IN INNOVATIVE AND EDUCATIONAL ACTIVITY OF TECHNICAL UNIVERSITIES - A. A. Andrushevich; N. K. Tolochko; P. S. Chugayev (Литьë и металлургия)
Functional abilities of computer microscopes are considered. Prospects of application of computer microscopy in scientific and innovative and educational activity of technical colleges are discussed.